2019
DOI: 10.1021/acs.orglett.9b02900
|View full text |Cite
|
Sign up to set email alerts
|

One-Pot Conversion of Allylic Alcohols to α-Methyl Ketones via Iron-Catalyzed Isomerization–Methylation

Abstract: A one-pot iron-catalyzed conversion of allylic alcohols to α-methyl ketones has been developed. This isomerization−methylation strategy utilized a (cyclopentadienone)iron(0) carbonyl complex as precatalyst and methanol as the C1 source. A diverse range of allylic alcohols undergoes isomerization−methylation to form α-methyl ketones in good isolated yields (up to 84% isolated yield).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 83 publications
1
23
0
Order By: Relevance
“…To further demonstrate the usefulness of the Fe‐catalyzed procedure, the Morrill group showed that the process may be extended to allyl alcohols, resulting in products with moderate to excellent yields (Scheme 7 d, below). [30] During methylation with CD 3 OD there was near complete incorporation of deuterium at the α‐ and for 54 % at β‐position. This percentage of 54 % can be understood when an iron hydride, formed by dehydrogenation of allyl alcohol or methanol, is involved in the mechanism.…”
Section: [D 4 ]Methanolmentioning
confidence: 99%
See 1 more Smart Citation
“…To further demonstrate the usefulness of the Fe‐catalyzed procedure, the Morrill group showed that the process may be extended to allyl alcohols, resulting in products with moderate to excellent yields (Scheme 7 d, below). [30] During methylation with CD 3 OD there was near complete incorporation of deuterium at the α‐ and for 54 % at β‐position. This percentage of 54 % can be understood when an iron hydride, formed by dehydrogenation of allyl alcohol or methanol, is involved in the mechanism.…”
Section: [D 4 ]Methanolmentioning
confidence: 99%
“…The complex showed good reactivity towards the selective β‐methylation of substituted 2‐arylethanol derivatives. To further demonstrate the usefulness of the Fe‐catalyzed procedure, the Morrill group showed that the process may be extended to allyl alcohols, resulting in products with moderate to excellent yields (Scheme 7d, below) [30] . During methylation with CD 3 OD there was near complete incorporation of deuterium at the α‐ and for 54 % at β‐position.…”
Section: [D4]methanolmentioning
confidence: 99%
“…Next, Morrill and co‐workers [17] reported a one‐pot transformation of allylic alcohols to α ‐C‐methyl ketones. This reaction proceeded through isomerization‐methylation using Fe‐catalyst (1) (2 mol%) in the presence of Me 3 NO (4 mol%) and K 2 CO 3 (2 equiv.)…”
Section: Fe‐catalyzed C‐methylation Reactions Using Methanolmentioning
confidence: 99%
“…Subsequently, they developed a one‐pot synthesis of α ‐methyl ketones from the corresponding allylic alcohol applying an isomerization‐methylation strategy (Scheme 31A) [131] . Later, Renaud and co‐workers developed an α ‐alkylation to access β ‐disubstituted carbonyl compounds directly in presence of 11 a [132] .…”
Section: Alkylation Reactionsmentioning
confidence: 99%